2021
DOI: 10.1159/000512214
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Mathematical Arterialization of Venous Blood in Intensive Care and Pulmonary Ward Patients

Abstract: <b><i>Background:</i></b> Arterial blood gases are important when assessing acute or critically ill patients. Capillary blood and mathematical arterialization of venous blood have been proposed as alternative methods, eliminating pain and complications of arterial puncture. <b><i>Objectives:</i></b> This study compares the arterial samples, arterialized venous samples, and capillary samples in ICU and pulmonary ward patients. <b><i>Method:</i>&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Prior studies exploring the agreement between absolute arterial and v-TAC PaCO 2 values indicated a requirement for 41 matched samples at 80% power (β-level 0.20) and 5% significance (α-level 0.05). [8][9][10][11][12][13][14][15] We assumed a proportionate variability for the change in PaCO 2 in the absence of existing data, though aimed to recruit at least 80 patients. In addition to the lack of data, this was because some recruited patients would not require NIV; a review of admissions to our unit in the preceding year showed that 67% of patients assessed were treated with NIV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies exploring the agreement between absolute arterial and v-TAC PaCO 2 values indicated a requirement for 41 matched samples at 80% power (β-level 0.20) and 5% significance (α-level 0.05). [8][9][10][11][12][13][14][15] We assumed a proportionate variability for the change in PaCO 2 in the absence of existing data, though aimed to recruit at least 80 patients. In addition to the lack of data, this was because some recruited patients would not require NIV; a review of admissions to our unit in the preceding year showed that 67% of patients assessed were treated with NIV.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies exploring the agreement between absolute arterial and v-TAC PaCO 2 values indicated a requirement for 41 matched samples at 80% power (β-level 0.20) and 5% significance (α-level 0.05) 8–15. We assumed a proportionate variability for the change in PaCO 2 in the absence of existing data, though aimed to recruit at least 80 patients.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The method uses a mathematical algorithm to transform venous blood gas values to arterialized values (aVBG) by simulating the transport of blood back through the tissue [7]. The method has been investigated in different patient populations, including patients treated in emergency rooms, cardiorespiratory wards, and intensive care units [8][9][10][11]. Thereby, a close agreement between ABG and aVBG for pH (mean difference: 0.002; 95% limits of agreement [LoAs]: −0.025 to 0.029) and pCO 2 has been demonstrated (mean difference: −0.3 mm Hg; 95% LoAs: −4.2 to 3.6 mm Hg) [10].…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting that a physiological model, derived from first principles without training to data, can in this context behave as well as a statistical model trained to twothirds of these data, and which uses individual clinical variables over and above acidbase and oxygenation status (4). v-tac was previously tested on ICU patients, but using peripheral venous blood (50) where it worked with the same precision as with peripheral venous blood from non-critically ill patients. The reason results were not as expected when tested on central venous blood measured in study III could have been due to various reasons, primarily related to the presence of circulatory disturbances.…”
Section: The Use Of V-tac In a Critically Ill Population Using Centra...mentioning
confidence: 99%